2020
DOI: 10.3390/land9010023
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing Landscape-Scale Forest Cover Loss in the Democratic Republic of Congo (DRC) between 2000 and 2015

Abstract: Shifting cultivation has been shown to be the primary cause of land use change in the Democratic Republic of Congo (DRC). Traditionally, forested and fallow land are rotated in a slash and burn cycle that has created an agricultural mosaic, including secondary forest, known as the rural complex. This study investigates the land use context of new forest clearing (during 2000–2015) in primary forest areas outside of the established rural complex. These new forest clearings occur as either rural complex expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 49 publications
2
37
0
5
Order By: Relevance
“…REDD+ actors participating in our national consultation workshop felt this was key to prioritizing future actions across the DRC's various landscapes. Studies conducted by Tollens (2010), Peltier et al (2014), Tyukavina et al (2018), Lubamba (2019) and Molinario et al (2020) suggest that, in many parts of the DRC, deforestation is due to the expansion of smallholder cropland, firewood collection, construction and swidden agriculture, yet forestry and mining have greater potential to damage forest cover than local community practices do.…”
Section: Drivers Of Deforestation and Forest Degradationmentioning
confidence: 99%
“…REDD+ actors participating in our national consultation workshop felt this was key to prioritizing future actions across the DRC's various landscapes. Studies conducted by Tollens (2010), Peltier et al (2014), Tyukavina et al (2018), Lubamba (2019) and Molinario et al (2020) suggest that, in many parts of the DRC, deforestation is due to the expansion of smallholder cropland, firewood collection, construction and swidden agriculture, yet forestry and mining have greater potential to damage forest cover than local community practices do.…”
Section: Drivers Of Deforestation and Forest Degradationmentioning
confidence: 99%
“…Les études menées par Tollens (2010), Peltier et al (2014), Tyukavina et al (2018, Lubamba (2019) et Molinario et al (2020) suggèrent que dans de nombreuses régions du pays, la déforestation est due à l'expansion des petites exploitations agricoles, à la collecte du bois de chauffe, à la construction, à l'agriculture itinérante sur brûlis, mais aussi à l'exploitation forestière et minière qui constituent un potentiel destructeur bien plus important sur la couverture forestière que les pratiques des communautés locales.…”
Section: Facteurs De Déforestation Et De Dégradation Forestièreunclassified
“…Pourtant, le MEDD (2015a) rapporte que l'agriculture est la principale cause de déforestation. Ce point de vue est soutenu par Tyukavina et al (2018) et Molinario et al (2020), qui signalent que la perte forestière dans le bassin du Congo est dominée par l'augmentation du défrichement causé par les petits exploitants. Cependant, de nombreuses études, dont le rapport McKinsey de 2009, ont prédit qu'en 2015, 3,2 millions d'hectares de terres seraient déboisés pour le développement de projets agricoles industriels, y compris des plantations de palmiers à huile.…”
Section: L'agricultureunclassified
“…Recent studies have identified several anthropogenic land uses that contribute to forest loss, forest fragmentation and land degradation [ 9 , 10 ]. Agriculture has been identified as one of the factors contributing to forest change, especially in the tropical regions of the world [ 11 16 ]. Related to agricultural activities is logging, which also involves the removal of forest cover [ 17 – 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…fragmentation and land degradation [9,10]. Agriculture has been identified as one of the factors contributing to forest change, especially in the tropical regions of the world [11][12][13][14][15][16]. Related to agricultural activities is logging, which also involves the removal of forest cover [17][18][19].…”
Section: Introductionmentioning
confidence: 99%